X-raying educator-related factors hindering sexuality education implementation in rural South African schools: learners’ perspectives - Adekola, Ayobami Precious (Frontiers in Education, 2024)
Although numerous studies have demonstrated the effectiveness of well-implemented school-based sexuality education in promoting young people's sexual and reproductive health outcomes, the prevalence of teenage pregnancy among school-going adolescents in rural schools located in the King Cetshwayo District of South Africa suggests it fell short of its objectives of reducing learners' vulnerability, enhancing decision-making abilities, and raising self-efficacy in these schools. This study focused on learners' experiences with their schools' sexuality education programs.Methods: This was a qualitative, interpretative phenomenological study. Data was collected from 84 participants across nine schools in the study setting using focus group interviews. An Interpretative Phenomenological Analysis framework was followed to analyze the data.The results of the study showed that educator-centered impediments to effective school-based sexuality education included attitudes, beliefs, age differences, health status, prior experiences, and personal discomfort. The results further indicated that these obstacles have a detrimental effect on the pedagogical effectiveness of sexuality education teachers in implementing the curriculum in the study setting and, consequently, on the sexual well-being of the learners.Based on the study's findings, pre-service sexuality education pedagogy training is recommended for student teachers, as well as ongoing in-service training and re-training interventions and support for sexuality education teachers, to address the identified barriers and improve their pedagogical efficacy.